Enhancing Economic Resilience through Innovation: The Development of Mbote Chips - Utomo, Dimas Satriyo; Brata, Diah Puji Nali; Musnaini, Musnaini; Ulya, Fahimatul (Bisma : Bimbingan Swadaya Masyarakat, 2024)
This community service project aims to explore the potential of mbote (taro) as a value-added product to enhance economic resilience during the COVID-19 pandemic. The project focuses on transforming traditional mbote into mbote chips and improving the branding and marketing strategies of local sellers in Pabean Sedati Village, Sidoarjo Regency. Participatory Action Research (PAR) methodology was applied to assist sellers in developing unique packaging, creating brand identity, and utilizing online platforms for marketing. The results indicate that the innovation positively impacted product visibility, consumer engagement, and business sustainability despite the economic challenges posed by the pandemic. The project demonstrates the effectiveness of small-scale innovations in enhancing the market competitiveness of local agricultural products and provides a model for rural entrepreneurship during crisis periods.